Microstructural evolution and mechanical properties of magnesium alloy/austenitic stainless steel joints produced by resistance spot welding techniques / Sunusi Marwana Manladan - Sunusi Marwana , Manladan (2017)
Multi-material design is gaining prominence as an efficient strategy to reduce the weight of vehicles, improve crash-worthiness, balance cost, and reduce environmental pollution. Mg alloys and austenitic stainless steels (ASS) have been identified as excellent candidates for next generation vehicle structures. Therefore, it is imperative to develop reliable means of joining them together. Resistance spot welding (RSW) is the most widely used sheet joining process. However, joining Mg alloys to steel by RSW is extremely challenging due differences in physical and metallurgical properties. In this research, different RSW techniques, namely, resistance element welding (REW), resistance spot weld bonding (RSWB), and resistance element weld bonding (REWB), were employed to join 1.5-mm-thick AZ31 Mg alloy and 0.7-mm-thick 316L ASS. For the purpose of comparison, RSW and adhesive bonding (AB) were also used. The microstructural evolution and mechanical properties of the joints were characterized using optical microscopy, scanning electron microscopy, energy dispersive spectroscopy, micro-hardness, and tensile-shear tests. The RSW joints were found to be produced through welding-brazing mode, in which the Mg alloy melted and spread on the solid ASS, forming a nugget only in the Mg alloy. The microstructure of the nugget consisted of only columnar dendritic structure, indicating that columnar-to-equiaxed transition was interrupted. Shrinkage porosity and cracking were also observed in the nugget. In contrast, a two-zone nugget was formed during REW, consisting of a peripheral nugget on the ASS side and the main nugget. The macroscophic morphology and microstructures of the RSWB and REWB joints were similar to those of traditional RSW and REW joints, respectively. However, compared with the RSW and REW joints, the RSWB and REWB joints possessed larger bonding diameter and nugget diameter, respectively. Overall, the traditional RSW joints exhibited inferior mechanical performance with a peak load of 2.23 kN and energy absorption of 1.14 J. The REWB joints possessed the best performance, with outstanding energy absorption. Compared with the RSW joints, the REWB joints showed 238 % higher peak load and 51 times higher energy absorption; RSWB joints showed 187 % higher peak load and 24 times higher energy absorption; AB joints showed 111% higher peak load and 7 times higher energy absorption; and REW joints showed 66% higher peak load and 9 times higher energy absorption. Irrespecive of the welding current, the RSW joints failed in interfacial failure mode, while the failure mode of REW joints transited from interfacial to pullout mode with increase in welding current. The RSWB joints exhibited a hybrid failure mode comprising of delamination at the Mg/adhesive interface, cohesive failure in the adhesive, and interfacial failure. With increase in welding current, the failure mode of the REWB joints changed from hybrid failure mode involving delamination at both the Mg/adhesive and adhesive/ASS interfaces, cohesive, and pullout failure to a hybrid failure involving delamination at Mg/adhesive interface and failure in the Mg alloy. Therefore, RSWB and especially REWB could be reliable techniques for joining Mg alloy and stainless steels to obtain high peak load, outstanding energy absorption, and favorable failure mode.